Dual Binding of an Antibody and a Small Molecule Increases the Stability of TERRA GQuadruplex - Yangyuoru,PM; DiAntonio,M; Ghimire,C; Biffi,G; Balasubramanian,S; Mao,H (Angewandte Chemie, 2015)
Abstract In investigating the binding interactions between the human telomeric RNA (TERRA) Gquadruplex (GQ) and its ligands, it was found that the small molecule carboxypyridostatin (cPDS) and the GQselective antibody BG4 simultaneously bind the TERRA GQ. We previously showed that the overall binding affinity of BG4 for RNA GQs is not significantly affected in the presence of cPDS. However, singlemolecule mechanical unfolding experiments revealed a population (48 %) with substantially increased mechanical and thermodynamic stability. Forcejump kinetic investigations suggested competitive binding of cPDS and BG4 to the TERRA GQ. Following this, the two bound ligands slowly rearrange, thereby leading to the minor population with increased stability. Given the relevance of Gquadruplexes in the regulation of biological processes, we anticipate that the unprecedented conformational rearrangement observed in the TERRAGQ–ligand complex may inspire new strategies for the selective stabilization of Gquadruplexes in cells.